On Matrix and Determinant Identities for Composite Functions (Journal of Computational Mathematics, 2018)
We present some matrix and determinant identities for the divided differences of the composite functions, which generalize the divided difference form of Faà di Bruno's formula. Some recent published identities can be regarded as special cases of our results.
Keywords: Bell polynomial; Composite function; Determinant identity; Divided difference; Matrix identity.